Longitudinal and Transverse Electron Scattering Form Factors for 13C Nucleus with Core-Polarization Effects - Adeeb, N.; Alzubadi, A.; Jalal, O. (Iraqi Journal of Science, 2024)
Inelastic electron scattering have been studied for (3.68 )2123MeV,(7.55 )2125MeV(15.11 )2323MeVstates in the 13C nucleus. 4He is considered as an inert core withnine nucleons out of it (the model space of nucleus). Form factors are calculated byusing Cohen-Kurath interaction for 1p-shell model space with Modified SurfaceDelta Interaction (MSDI) as a residual interaction for higher configuration. Thestudy of core-polarization effects on the form factors is based on microscopictheory, which combines shell model wave functions and configurations with higherenergy as the first order perturbation. The radial wave functions for the singleparticlematrix elements have been calculated with the harmonic oscillator potentialand the oscillator length parameter b is chosen to reproduce the measured root meansquare charge radius for nucleus under considered in this work. The inclusion of thecore-polarization effects (the effects from out of the core) gives a good agreementwith the experimental data.